Reis e rainhas negros no mundo atlântico - Kraay, Hendrik (Afro-Ásia, 2023)
Resenha de: VALERIO, Miguel A. Sovereign Joy: Afro-Mexican Kings and Queens, 1539-1640. Cambridge: Cambridge University Press, 2022. 264 p.